Companion Proceedings of the Web Conference 2020 2020
DOI: 10.1145/3366424.3382186
|View full text |Cite
|
Sign up to set email alerts
|

Capturing Evolution in Word Usage: Just Add More Clusters?

Abstract: The way the words are used evolves through time, mirroring cultural or technological evolution of society. Semantic change detection is the task of detecting and analysing word evolution in textual data, even in short periods of time. In this paper we focus on a new set of methods relying on contextualised embeddings, a type of semantic modelling that revolutionised the NLP field recently. We leverage the ability of the transformer-based BERT model to generate contextualised embeddings capable of detecting sem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 19 publications
0
55
0
Order By: Relevance
“…Jensen-Shannon divergence (JSD). In this measure, influenced by Dubossarsky et al (2015), Martinc et al (2020) and , word usage matrices from two time periods are first stacked into one matrix. Then, we standardize the vectors and obtain word usage clusters of token embeddings using the Affinity Propagation clustering algorithm (Frey and Dueck, 2007).…”
Section: Contextualized Embeddingsmentioning
confidence: 99%
“…Jensen-Shannon divergence (JSD). In this measure, influenced by Dubossarsky et al (2015), Martinc et al (2020) and , word usage matrices from two time periods are first stacked into one matrix. Then, we standardize the vectors and obtain word usage clusters of token embeddings using the Affinity Propagation clustering algorithm (Frey and Dueck, 2007).…”
Section: Contextualized Embeddingsmentioning
confidence: 99%
“…There also exist clustering methods that select the optimal K automatically, e.g. DBSCAN or Affinity Propagation (Martinc et al, 2020). They nevertheless require method-specific parameter choices which indirectly determine the number of clusters.…”
Section: Usage Typesmentioning
confidence: 99%
“…This provides new opportunities for diachronic analysis: for example, it is possible to group similar token representations and measure a diversity of such representations, while predefined number of senses is not strictly necessary. Thus, currently there is an increased interest in the topic of language change detection using contextualized word embeddings [9,10,14,21,27,28].…”
Section: Contextualized Word Embeddingsmentioning
confidence: 99%
“…[27] used averaged time-specific BERT representations and calculated cosine distance between averaged vectors of two time periods as a measure of semantic change. [28] tested Affinity Propagation algorithm for usage clusterization and showed that it is consistently better than k-Means. Finally, [21] applied approaches similar to [10], but also analyzing ELMo models and adding cosine similarity of average vectors as a measure.…”
Section: Contextualized Word Embeddingsmentioning
confidence: 99%